Propriedades funcionais da linhaça (Linum usitatissimum L.) em diferentes condições de preparo e de uso em alimentos - Marques, Anne Y Castro (2008)
The world population has been showing more concern for the food and its constituents, encouraging the food industry to invest in healthy products and in functional foods. Among those considered functional foods is the flaxseed (Linum usitatissimum L.), a small grain of ovate shape with high nutritional value by being a good source of fiber, essential fatty acids and protein. The aim of this study was observe the flaxseed functional properties in different processing conditions and use in food, through the determination of the grain chemical composition, biological response in rats and the fatty acids profile. The chemical determination was found that flaxseed used in this study is rich in lipid (37,04 g%), in protein (16,69% g) and in fiber (32,9 g%). In the biological trial, 32 male Wistar rats received four diet types (P: diet standard as AIN; LC: diet with 16% of raw flaxseed; LA: diet with 16% of roast flaxseed; and OL: diet with flaxseed oil), it was found that the use of raw flaxseed, roast flaxseed and flaxseed oil resulted positively in vivo. There was a decrease in biochemical blood glucose, triglyceride and total cholesterol levels, and increase the fecal excretion and lipid excretion, no change in the growth of rats in treatments with flaxseed. The more positive data were detected in animals feed with the raw grain. By gas chromatography analysis was carried out of the grain and flaxseed oil lipid profile subjected to different processes involving high temperatures: raw grain (LC); grain baked in electric oven to 150ºC for 40 minutes (L150); grain baked in electric oven to 180ºC for 40 minutes (L180); grain heated in microwave oven (LM); flaxseed oil (OL) and flaxseed oil heated to 180ºC for 30 minutes (OF).Changes in the saturated and unsaturated fatty acids were detected, but the flaxseed and the flaxseed oil remained significant amounts of polyunsaturated fatty acids, mainly of Y- linolenic acid, in all treatments. Despite the minor benefits caused by flaxseed processing (baked grains or as oil), it was noted that part of Y-linolenic acid remains in the food and is absorbed by the organism. In conclusion, it is possible to state that flaxseed is still quite stable when subjected to various processes involving high temperatures and it is an alternative source of Y-linolenic acid. However more studies are needed to provide the appropriate doses for humans, according to the particular individual.